PH-stat vs. free-fall pH techniques in the enzymatic hydrolysis of whey proteins. (15th May 2016) - Fernández, Ayoa; Kelly, Phil
Highlights: pH-stat at optimum pH does not always imply the fastest enzymatic proteolysis rates. WPI is hydrolysed faster by Protamex® under free-fall pH conditions than using pH-stat. β-lg degradation rate using Protamex®: free fall pH > pH-stat (KOH) > pH-stat (NaOH). Potassium acts as cofactor for the activity of Bacillus subtilis enzyme preparations. Abstract: Enzymatic hydrolysis of a commercial whey protein isolate (WPI) using either trypsin or Protamex® was compared using controlled (pH-stat) and uncontrolled (free-fall) pH conditions. pH-stat control at the enzyme's optimum value led to a more rapid rate of WPI hydrolysis by trypsin, while the opposite was the case when Protamex® was used. Furthermore, the choice of alkaline solution used to maintain constant pH during pH-stat experiments appeared to affect the reaction rate, being higher when KOH is added to the reaction mixture instead of NaOH. It would appear that potassium may play a role as co-factor or activator for the activity of this particular protease preparation. Although pH-stat techniques are usually considered to yield better hydrolysis kinetics, these findings suggest that the response of proteolytic enzyme preparations to static or free-fall pH control should be checked in advance, particularly when undertaking large scale production of WPI hydrolysates.